A ROLE OF SOME ESCHERICHIA COLI – VIRULENCE FACTORS IN CAUSING VAGINOSIS - Hawraa N Hameed; Suhad S Mahmood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Bacterial vaginosis, also known as BV, is a condition that is frequently associated with vaginal inflammation and can be caused by changes in the bacterial composition of the vaginal microbiome. It is the most common vaginal infection among women of reproductive age. The goal of this study is to determine the antibiotic resistance and the role of some virulence genes of E. coli isolates in the vaginosis of non-pregnant women (16–45 years old) as well as the stool of the same patient. A total of 160 samples were collected (130 vaginal swab samples and 30 samples from the stool). All isolates have been identified by MacConkey and Eosin methylene blue media, biochemical tests, and PCR detection of the UidA gene. Just 50 isolates were diagnosed and confirmed as E. coli bacteria. Resistance to piperacillin was most frequently observed in 31 isolates (62%), followed by cefuroxime and cefixime in 28 isolates (56%). The polymerase chain reaction was used to detect virulence genes (FimH and IutA), and the results showed that both genes were present in 94% and 97% respectively of the isolates.